The fungal flora associated with black spot of pineapples,Some aspects of the microflora of citrus soils - Edmonstone-Sammons, Chloris (Rhodes University, Faculty of Science, Botany Department, 1956)
The earliest reference to investigations of "black spot" in pineapples is made by Tryon (1898), who refers to the work of Dr A. A. Brown (1896) of the stock Branch, Victoria (Aus.), who sectioned diseased areas of pineapples and found fungal spores and hyphae in the tissues. The symptoms of this socalled "fruitlet core rot," are described by Tryon as: "well defined dark brown markings immediately beneath the surface, and passing inwards to a depth of 1/4" to 1/2"- the malady commencing in separate fruitlets, the central core of the fruit remaining quite healthy." (This description agrees with the symptoms referred to as "black spot" 1n this country). Subsequent culture of the spores (found by Brown) on slices of healthy fruit resulted in growth of Mucor racemosus. Brown regarded an invasion by this fungus as a primary cause of the disease. Intro. p. 1.
Keywords: Fungi; Pineapple -- Diseases and pests; Citrus -- Diseases and pests; Citrus -- Soils